Development of e-journal system in South Aceh Polytechnic using web based application. Issue 1 (January 2021) - Asmaidi,; Ihsan, M A; Putra, D S; Zulfa, M; Rusnanda, R; Kartawijaya, M
Abstract: Student publication organizing application is an application used to assist officers in the process of managing web-based student publication journals. The mechanism of this research was made iteratively from the process of making software requirements specifications, analyzing system requirements, then proceed to the system design stage, use case and flowchart design, database design, and interface design, then followed by developing applications and closed with testing. The programming languages used are PHP, HTML, and MySQL databases. The results of this study are the document design and application organizing of student publications. The application of this student publication organizing application can improve the quality of the scientific journal organizing process at the South Aceh Polytechnic more systematic and organized to achieve efficiency and improve publication to be global.